L’occupation des zones à risques d’inondation dans le district d’Abidjan : entre représentations, frustrations et rhétoriques - Métogba Fofana; Kouamé Walter Kra (VertigO, 2025)
This article examines the human occupation of “risk zones” in Abidjan, characterized by the triple threat of flooding, landslides and electrocutions. Beyond the socio-economic factors, the trivialization of risk and urban growth noted in the literature, it explores the social imaginations as the foundations of this illegal and prohibited occupation. Qualitative survey data collected on five of the most at-risk sites in the Abidjan district from occupants and through semi-directed individual interviews, focus groups and direct observation, were the subject of a thematic content analysis. The results reveal three main illegal and anarchic processes of occupation of risk areas in Abidjan: the purchase of land to build houses, the rental of land to build houses and the illegal rental of already built housing. Four factors underlie this disorderly and illicit occupation: the reinterpretation by the occupiers of the laxity of the urban land management authorities as a sign of weakness; the conviction that this irregular occupation remains the only housing option notwithstanding a common awareness of the risk among the occupants; the widespread social frustration among them and fueled by what they consider to be a “failure” of public social housing policy; and finally the rhetoric of collective immunity against the risk of disaster. In short, there are real inadequacies in the governance of urban space, which requires a double necessity: communicating differently about flood risks and rethinking public policy for social housing.